Inventory accounting analysis at pt. Andalas independent son of Pekanbaru - Darmi Darmi (Institute of Accounting Research and Novation (IARN), 2023)
PT. Andalas Putra Mandiri is a trading company engaged in the sale of medicines and medical devices, which is located at Jalan Thamrin No.124, Sukamaju sub-district, Sail sub-district, Pekanbaru City. For companies, inventory is the largest item in the financial statements and absorbs very large investments. This makes the writer feel the need to conduct research based on Financial Accounting Standards No. 14 relating to the presentation of inventory estimates in the financial statements, with the title